Nature of gene action for yield and its components in mungbean (Vigna radiata) - PATHAK, N; SINGH, M N; MISHRA, M K; SAROJ, S K (The Indian Journal of Agricultural Sciences, 2015)
The assessment of gene effect for some yield characters and detection of epistasis in mungbean [Vigna radiata (L.) Wilczek] was studied in four crosses involving five parents through generation mean analysis during kharif 2012 at Banaras Hindu University (BHU), Varanasi, UP. Six populations, viz. P1, P2, F1, F2, B1 and B2 of four crosses involving five parents were evaluated. The nature and magnitude of gene effects for yield and its components in mungbean was studied using six parameter model of generation mean analysis. The presence of epistasis was detected by joint scaling test and inadequacy of additive-dominance model was established except seeds/pod. Additive (d), dominance (h) gene effects along with one or more type of non-allelic interactions (i, j, l) contributed significantlytowards the inheritance of all the quantitative characters in majority of the crosses. Duplicate type of epistasis andpredominant dominance effects was also prevalent in most of the cases except in days to maturity in HUM 8 x ML 713 cross. Thus, postponement of selection in later generations may be suggested to obtain transgressive segregants for improvement of mungbean populations.